The impact of financial innovation on banking regulation. Evidence from the global financial crisis - Baicu, Claudia Gabriela (Annals of Spiru Haret University. Economic Series, 2011)
The development of financial innovations in a fast pace led to increased efficiency of the financial system, but raises some issues regarding the regulation and supervision of financial activity. The latest example is the global financial crisis, which has pointed out the negative role played by the financial innovations of credit risk transfer on the stability of the financial system. Starting from the above, the article herein is structured in the following sections: the first one reviews the decisive factors of the financial innovation, the second one highlights the role of the financial innovations in the global financial crisis and the final one refers to the impact of the financial innovations on the financial regulation and supervision.